Defining interactions between Mycobacterium leprae and Langerhans cells - Fletcher, Darcy, author; Belisle, John, advisor; Henao-Tamayo, Marcela, committee member; Hess, Ann, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2021)
Leprosy is a chronic infection that affects the skin and peripheral nerves. Written accounts of the disease date back to at least 600 BC. Mycobacterium leprae, the causative agent of leprosy was first discovered by Dr. Gerhard Armauer Hansen in 1873. Leprosy remains a major health problem in several low- and middle-income countries including Brazil, India, and Indonesia. There are numerous clinical presentations of the disease which presents many challenges for controlling the disease including diagnosis, treatment regimen and duration, and occasional instances of drug resistant cases. Further challenges exist in studying the disease, knowledge of the intricate interactions with innate immune cells has made advances in some cell subsets but is limited in others leaving an incomplete picture of the disease. These gaps limit advances in disease management. M. leprae is an obligate, intracellular pathogen that grows preferentially between 33-35° C and selectively invades peripheral nerves and skin-resident innate immune cells including macrophages. Numerous host cells including macrophages and Schwann cells have been studied to understand their interaction with M. leprae, but other skin-resident immune cells like dendritic cells, specifically Langerhans cells, have not been studied as extensively. The findings that M. leprae antigens can be presented via CD1a on Langerhans cells has spurred interest in understanding how Langerhans cells interact and uptake M. leprae leading to downstream effects on T cell activation and overall immune responses. The hypothesis of this study is that M. leprae interacts with Langerhans cells via various cell surface receptors that influence a Th1 or Th2 immune response. This study interrogates the complex interactions between Mycobacterium leprae and Langerhans cells via multiple cell surface receptors. In Chapter 2, an ex vivo optical tissue clearing method was modified for fragile skin samples to analyze innate cell recruitment to the site of infection. Colocalization between Langerhans cells and a closely related mycobacterial spp. to M. leprae, M. haemophilum, was observed in a 3D optically cleared tissue. These observations indicate that wholistic insight of bacteria/innate immune cell interactions can be gleaned using experimentally infected tissues or human skin biopsies. Chapter 3 presents the contributions from multiple cell surface receptors present on Langerhans cells in recognizing and binding M. leprae. Langerin was found to play a role in binding M. leprae, however, was not the only cell surface receptor involved in recognition of M. leprae. CD5+ Langerhans cells can be separated into CD5high and CD5low LCs that have differences in binding capacity for M. leprae. This study builds the foundation to explore the wholistic contributions of Langerhans cells interactions and uptake of M. leprae. Further work should be conducted to identify M. leprae ligand(s) for CD5 and downstream effects on cytokine secretion and T cell activation.